[Wielkanocna karta okolicznościowa z królikiem i kogutem] . Easter greeting card with a bunny and a rooster - Solidarność Nauczycielska. (Solidarność Nauczycielska, 1985)
Red and black print on white paper. Undivided back with b&w print. Easter greeting card contains a graphic image which represents a rooster and a bunny. On the back, the card contains date, place of issue and the issuing agency, with greetings "May the day of the Resurrection of the Lord approximate the day of the Resurrection of the nation."